An integrative approach in treating complete food refusal in children: a case study - Ismail, Khamsiah; Abd Hamid, Siti Rafiah (2015)
Eating disorders among children may be attributed to the range of complications associated with feeding problems: from mild (e.g.. missed meals) to total food rejection. Many early feeding problems can be diagnosed and corrected either by medical interventions, therapies or behavioural modification. Parents might use reward system in persuading them to eat and in extreme cases- pressure. force and punishment are also applied. There are also cases of children who do not eat at all and simply refuse to eat. For parents of children with feeding disorders, this is the beginning of a long and challenging journey that will include many medical and clinical experts. This paper presents the case study of a l3-year old boy with borderline autism, dyslexia and ADHD who did not consume any food at all i.e. complete food refusal for the first 12 and a half years of of his life. In his treatment strategies, the therapist utilized a combination of several interventions strategies based on a few theoretical approaches. This integrative approach designed for his treatment intervention was divided into four phases comprising of: (i) Person-Centred; (ii) Behavioural Therapy; (iii) Cognitive Behavioural Therapy; and (iv) Psycho-educational. His family was also involved in the treatment. This study found that the approaches used in the treatment helps to improve the boy's eating problem as he started to eat pureed and soft food such as porridge. The therapy has also helped him gained self-confidence and improved his communication as well as social skills. He u,as healthier as he had not been admitted to hospital after the therapy ended. The findings of this study provide evidence that eating disorder problem involving children can be treated with psychotherapy. The treatment plan can be utilized to initiate suitable intervention as an effort to help children as well as adolescents manages their eating problems.